Activated Empty Palm Fruit Bunch for the Adsorption of Heavy Metal Ions: Kinetics and Thermodynamics - Ekeoma, B.C. (Iranian Chemical Society, 2022)
The efficacy of activated empty palm fruit bunch as an adsorbent for the uptake of copper, iron, and zinc heavy metal ions was investigated and the effects of temperature and contact time on adsorption capacity were studied. Samples of electroplating waste stream and waste vegetable oil were used and the optimum temperature for the adsorption process in both samples was determined to be 25 °C while the respective optimum contact times were 30 and 40 min. Linear regression analysis showed that the Langmuir isotherm model gave the best fit to the equilibrium adsorption data of the investigated heavy metal ions. Using Cu(II) adsorption from the electroplating waste and waste oil samples as a case study, the Langmuir isotherm gave the highest R2 values of 0.9999 and 0.9998 respectively. The equilibrium adsorption capacity was determined to be 8.4 mg g-1 for the electroplating waste sample and 7.327 mg g-1 for the waste oil sample using the data for Fe(III) adsorption. The kinetics of the adsorption process was evaluated and the pseudo-second-order kinetic model provided the best description of the adsorption process in both samples according to the obtained R2 values from linear regression analysis. Thermodynamic parameters (AG°, AH°, AS°) were also calculated which together with other theoretical basis proved the adsorption mechanism in both samples to be physical. Results showed that adsorption was exothermic and spontaneous in both samples with AH° for the electroplating waste and waste oil samples calculated to be -1.14 x 10-2 kJ mol-1 and -1.68 x 10-3 kJ mol-1, respectively. © 2022. All Rights Reserved.